Efficacy of Misoprostol versus Syntometrine in the Prevention of Postpartum Hemorrhage - Sehrana Kousar , Farah Rehana, Farzana Kazmi (Journal of Rawalpindi Medical College, 2010)
effects of oral misoprostol versus syntometrine for prevention of primary postpartum hemorrhage. Methods: Interventional study; Eighty patients were divided into two equal groups. Misoprostol 600 microgram single dose was given orally immediately after cord clamping to Group A. Syntometrine (consists of 10 IU oxytocin + 0.5mg ergometrine) was given intravenous to Group B. Patients were kept under observation for 6 hours. Pulse, blood pressure, temperature any need for other uterotonic drugs, estimated blood loss (<500ml or >500ml) haemoglobin percentage 6hours before and after delivery, need for blood transfusion, side effects, time and mode of delivery were noted. Results: Differences in blood pressure and transfusion were statistically insignificant between two groups. Shivering and pyrexia was more common in Group A , and nausea, vomiting and hypertension in Group B Conclusion: Like syntometrine, misoprostol can be used prophylactically orally during third stage of labour to reduce the incidence of Primary postpartum hemorrhage.